Diverse clinical presentation of primary spontaneous pneumothorax in patients with pectus excavatum - Lee, June; Jeong, Jin Yong; Suh, Jong Hui; Park, Chan Beom; Kim, Dulee; Park, Soo Seog (Frontiers in Surgery, 2023)
Objective: Patients with primary spontaneous pneumothorax (PSP) tend to be young, tall, and thin, as do those with pectus excavatum (PE). Notably, the Haller index, which measures the severity of PE, tends also to be higher in patients with PSP, further suggesting a potential predisposing factor for the development of PSP in individuals with PE. This study aimed to share clinical experiences with case series of concomitant PSP and PE and to emphasize the importance of evaluating these two conditions together.In this single-center study, we conducted a retrospective records review to identify patients who were diagnosed and treated (including surgical or conservative treatment and follow-up observation) for the diagnosis of PE between July 2011 and February 2023. From these, we selected patients who were diagnosed with both PE and PSP and analyzed their clinical presentations.Results: Among a total of 139 patients with PE, there were 8 (5.76%) who had concurrent diagnoses of PE and PSP and who underwent surgery for PSP, PE, or both. The average age of these 8 patients (male:female = 7:1) was 19.38 years. The 8 patients were grouped into four categories based on their clinical scenarios. Group A had 1 patient with PE diagnosed first, followed by the discovery of PSP during evaluation; Group B included 2 patients initially presenting with PSP and subsequently diagnosed with PE during evaluation; Group C consisted of 1 patient who had PSP before undergoing surgical PE correction; and Group D comprised 4 patients who developed PSP after PE correction.The incidence of PSP in patients with PE was 5.76% (8 out of 139 patients), indicating the importance of vigilant monitoring for PSP prior to PE surgery, and vice versa. Furthermore, the authors recommend close observation for PSP independent of PE surgery, even in the absence of postoperative complications.